(untitled) - Brown, Roger J. (Amsterdam, 2005)
This book is designed as a supplementary text for upper division undergraduate and graduate real estate investment courses. The CD-ROM included with the book contains spreadsheets for data analysis tailored specifically to real estate settings.
Keywords: Real estate investment,Real estate investment,Đầu tư bất động sản,Đầu tư bất động sản; Decision making.,Planning,Ra quyết định,Lập kế hoạch